Impact of Geopolitical Risk on the Maritime Supply Chain: A Regional Analysis of the Effects on Global Trade - Dawar, Ashraf; Bai, Yang (International Journal of Supply Chain Management, 2024)
Geopolitical risks have a substantial impact on the disruption of maritime supply chains, leading to economic, logistical, and security challenges. This study scrutinizes the multifaceted relationship between geopolitical risks and disruptions in maritime supply chains, with a concentration key influences and their consequences. The research syndicates case studies, data analysis, and current affairs, to provide a comprehensive examination of the matter. The findings highlight that geopolitical risks, such as political instability, conflicts, terrorism, and trade disputes, can disrupt maritime supply chains in numerous ways. These disruptions can be apparent as port closures, commotions like shipping routes, increased insurance expenses, and heightened security dealings. Such disruptions have extensive significance including amplified costs, abridged reliability, supply chain blockages, and a negative influence on international trade streams. The novelty of the study is that it takes a regional approach, inspecting how geopolitical risk influences the maritime supply chain in different geographical areas. This provides a more nuanced and universal understanding of the matter, beyond just a state perspective.